Evaluating the EVA surgical navigation system for ureteral identification in an in vivo porcine model - Veronica Penza; Domenico Soriero; Beatrice Sperotto; Alberto Neri; Jesus Ortiz; Davide Pertile; Lorenzo Epis; Giacomo Carganico; Marco Amisano; Stefano Scabini; Darwin G. Caldwell; Leonardo S. Mattos (Scientific Reports)
Abstract Surgical safety has emerged as a significant public health concern. Ureteral injury (UI) is one of the most common forms of iatrogenic urological issues, lacking non-invasive prevention strategies. In this context, computer-assisted technologies offer a promising solution for enhancing intra-operative safety. This paper presents an in-vivo study focused on evaluating the feasibility of using an augmented reality (AR) surgical navigation system (EVA) for intra-operative ureteral identification on an animal model. An experienced surgeon performed a technical assessment of the system. The clinical evaluation was conducted by four general surgeons tasked with identifying the left or right ureter, both with and without EVA. The technical assessment highlighted that EVA is easily integrable with operating room instruments, achieving a calibration accuracy of $$1.7~\text {cm} ± 0.002$$ , and the virtual ureter effectively overlapping with the real ureter. The questionnaires indicated that surgeons appreciated EVA, with a $$SUS_{score} = 73.75$$ . The perceived mental demand, task complexity, and distractions were lower when using the EVA system. Future work will focus on increasing the number of subjects and exploring the efficacy of the system on other clinical tasks.